Предмет: Алгебра,
автор: volkovasadovskaya
Зная, что a^2 - 3a + 1 =0, найдете значение выражения a^6 + 1/a^6
Ответы
Автор ответа:
1
а^2-2a-6=0
D=4+24=28
a1=2+ \sqrt{28} /2=2+2 \sqrt{7} /2=1+ \sqrt{7}
a2=2- \sqrt{28} /2=2-2 \sqrt{7} /2=1- \sqrt{7}
Через a1:
(1+ \sqrt{7} )^2-2*(1+ \sqrt{7} )-6=1+2 \sqrt{7} +7-2-2 \sqrt{7} -6=1+7-2-6=0
Через a2:
(1- \sqrt{7} )^2-2*(1- \sqrt{7} )-6=1-2 \sqrt{7} +7-2+2 \sqrt{7} -6=1+7-2-6=0
Ответ: 0.
Похожие вопросы
Предмет: Физика,
автор: aandreyanov08
Предмет: Алгебра,
автор: nastasia56778
Предмет: Русский язык,
автор: lenok2473
Предмет: Математика,
автор: кошка195